2018
DOI: 10.15421/021804
|View full text |Cite
|
Sign up to set email alerts
|

Promising new fixed combination for the treatment of diseases of the hepatobiliar system: Substantiation of pharmacotherapeutic properties and pharmaceutical quality profile

Abstract: In this review article an analysis of literature data on the pharmacological and clinical study of a fixed combination of medicinal substances (artichoke leaf extract, ursodeoxycholic acid, taurine, and Angelica sinensis roots extract), as well a scientific substantiation of the pharmaceutical quality profile of the corresponding finished solid dosage form has been conducted. Chronic diseases of the hepatobiliary system are some of the most common human diseases and inferior only to atherosclerosis . The fact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…4 The reducing effect of UDCA on TSB could also be attributed to its ability to protect cholangiocytes from the cytotoxic effect of hydrophobic bile acids and improve the secretory function of hepatocytes. 39 Furthermore, this review identified that adding UDCA to PT in neonatal UH may decrease the duration of PT by 19.14 hours (95% CI: from −20.70 to −17.59).…”
Section: Discussionmentioning
confidence: 99%
“…4 The reducing effect of UDCA on TSB could also be attributed to its ability to protect cholangiocytes from the cytotoxic effect of hydrophobic bile acids and improve the secretory function of hepatocytes. 39 Furthermore, this review identified that adding UDCA to PT in neonatal UH may decrease the duration of PT by 19.14 hours (95% CI: from −20.70 to −17.59).…”
Section: Discussionmentioning
confidence: 99%